2013
DOI: 10.1590/s0104-11692013000700013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the concept Risk for Decreased Cardiac Output

Abstract: Objectives: to validate the concept "risk for decreased cardiac output". Method: Six of the eight steps suggested in the technique developed by Walker & Avant were adopted to analyze the concept of the phenomenon under study and the proposal made by Hoskins was used for content validation, taking into account agreement achieved among five experts. Results: the concept "decreased cardiac output" was found in the nursing and medical fields and refers to the heart's pumping capacity while the concept "risk" is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…(10) It is also seen that in this taxonomic classification system all diagnostic categories are derived from concepts and present theoretical models or formulations (11) to give meaning to the observations of physiological, psychic, social, religious and spiritual phenomena, going through continuous analyzes according to studies found in the literature. (12)(13)(14)(15)(16)(17)(18)(19) As already mentioned, the conceptual definition of powerlessness (00125) standardized by NANDA-I is "lived experience of lack of control over a situation, including a perception that one's actions do not significantly affect a result." (2) .…”
Section: Discussionmentioning
confidence: 99%
“…(10) It is also seen that in this taxonomic classification system all diagnostic categories are derived from concepts and present theoretical models or formulations (11) to give meaning to the observations of physiological, psychic, social, religious and spiritual phenomena, going through continuous analyzes according to studies found in the literature. (12)(13)(14)(15)(16)(17)(18)(19) As already mentioned, the conceptual definition of powerlessness (00125) standardized by NANDA-I is "lived experience of lack of control over a situation, including a perception that one's actions do not significantly affect a result." (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Esse DE está relacionado, principalmente, à diminuição da fração de ejeção do ventrículo esquerdo, resultando em sinais e sintomas como a dispneia, graças à incapacidade do coração em manter um débito cardíaco suficiente para satisfazer as necessidades teciduais de oxigênio, e edema nos membros inferiores, associado à presença do débito cardíaco, evidenciado pela infiltração no espaço intersticial e redução do fluxo sanguíneo periférico, associado à intolerância à atividade. (27,28) O risco de intolerância à atividade física é o DE destacado nas pessoas que correm o risco de não realizar atividade física suficiente ou completar uma rotina de atividade física regular. (24) É necessário que a assistência de enfermagem permita avaliar quais os possíveis fatores fisiológicos e motivacionais resultantes dessa intolerância, seja por estado de saúde comprometido ou ausência do autocuidado, tendo em vista as diversas doenças cardiovasculares que impossibilitam a realização de exercícios de alto impacto, o que permite a atuação de uma equipe multiprofissional para prestação da assistência qualificada.…”
Section: Discussão Discussãounclassified
“…Considering this perspective, a concept analysis of risk for decreased cardiac output (00240) was previously developed, consisting of its definition and validation by experts and the identification of its risk conditions in the literature. 10 This proposal was submitted to NANDA-I for possible recognition as a nursing diagnosis, approved and included in the 2015-2017 classification with the definition 'Vulnerable to inadequate blood pumped by the heart to meet metabolic demands of the body, which may compromise health' and six risk factors (alteration in heart rate, alteration in heart rhythm, altered afterload, altered contractility, altered preload and altered stroke volume; NANDA-I). 8 However, no previous study has investigated the predictive risk factors of the nursing diagnosis of risk for decreased cardiac output after CABG.…”
Section: Introductionmentioning
confidence: 99%